Art As a Dependable Driving Force In New Age Marketing - Esekong Andrew-Essien (Universitas Negeri Makassar, 2021)
Art has been a traditional marketing tool for ages. Visual and performing arts have been used for publicity, advertising, and marketing promotions in many media. With the advent of the internet and the integration of digital technology into the marketing process, the scope of marketing and its networks have extended. Technology has ushered in new-age marketing, which is the use of online and offline platforms to market goods, services, and ideas. Consequently, the extent of engagement of the arts in the process of marketing has expanded to address emerging needs. New-age marketing is electronically driven, with graphic arts as one of its central pivots. The graphic designer is therefore tasked to combine artistic skills with the offerings of digital technology, including social media networks towards attracting patronage from local and global domains. This paper reviews the structure and functionality of arts in general marketing; the increasing relevance of digital graphics in the complex of new-age marketing and strategies required to attract patronage for products, services, and ideas.